THE ROLE OF THE EDUCATION OFFICE IN IMPROVING THE QUALITY OF TEACHERS AND STUDENTS IN BANDA ACEH CITY - Denzi Aprial; Rahmattullah Rahmattullah; Rita Novita (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This paper discusses the crucial role of the Education Office in enhancing the quality of teachers and students in Banda Aceh City. The Education Office is responsible for implementing various strategies aimed at professional development for educators, including training programs, workshops, and certifications that equip teachers with modern pedagogical skills. Additionally, the office focuses on monitoring and evaluating educational practices to identify areas for improvement and ensure that educational standards are met. The provision of adequate infrastructure and learning resources is also emphasized, as these are essential for fostering an effective learning environment. Collaborative efforts with stakeholders, including NGOs, universities, and the private sector, are vital for creating a comprehensive support system for education. The paper further explores the enhancement of curricula to meet current societal needs, the promotion of student scholarships for underprivileged groups, and the empowerment of school committees to engage parents and communities in the educational process. Overall, this study highlights the multifaceted approach undertaken by the Education Office in Banda Aceh City to uplift educational quality and ensure sustainable development in the local education sector.